Schooling, Parents and Country - Ira N. Gang (Rutgers University, Department of Economics, 1997)
Our argument is that the importance of parent's schooling and female share of employment on children's schooling will vary by gender, ethnicity and economic system. We examine this issue across Germany, Hungary and the former Soviet Union. Our results indicate that there is a direct effect of economic system. Also, the slope coefficients vary among countries, ethnicity and gender. There are also differences in the human capital formation across ethnic groups and gender. While there is some assimilation across generations, it is far from complete.
Keywords: 330